Pengembangan Modul Bimbingan dan Konseling untuk Layanan Informasi Bahaya HIV/AIDS - Mochammad Arsyi Mughni; Hadi Pranoto; Mudaim Mudaim (Universitas Muhammadiyah Metro, 2025)
The purpose of this study was to develop and produce a product in the form of an information service module that can be used by grade XI students to help provide insight in the form of education about the dangers of HIV/AIDS. This type of research is development. The data subjects were Muhammadiyah Metro University Lecturers, Instructors and counselors as well as students participated in this study. The development process follows the ADDIE model. Before the research results, regarding the development of the Guidance and Counseling Module as an information service on the dangers of HIV/AIDS, it can be concluded that the HIV/AIDS information service This module serves as a student-friendly educational resource to enhance their knowledge and ideas. The results of this research can be used as teaching material for guidance and counseling educators. The findings from this research can be utilized as instructional material by guidance and counseling educators. in providing information services and becoming one of the learning facilities for class XI students.